Co-Treatment of Chloroquine and Trametinib Inhibits Melanoma Cell Proliferation and Decreases Immune Cell Infiltration - Degan, Simone; May, Brian L.; Jin, Yingai J.; Hammouda, Manel Ben; Sun, Huiying; Zhang, Guoqiang; Wang, Yan; Erdmann, Detlev; Warren, Warren; Zhang, Jennifer Y. (Frontiers in Oncology, 2022)
Autophagy is characterized as a cytoprotective process and inhibition of autophagy with medicinally active agents such as chloroquine (CQ) is proposed as a prospective adjuvant therapy for cancer. Here, we examined the preclinical effects of CQ combined with the MEK inhibitor trametinib (TRA) on melanoma. We found that cotreatment of CQ and TRA markedly slowed melanoma growth induced in Tyr-CreER.BrafCa.Ptenfl/fl mice. Immunostaining showed that trametinib decreased Ki-67+ proliferating cells, and increased TUNEL+ apoptotic cells. The combo treatment induced a further decrease of Ki-67+ proliferating cells. Consistent with the in vivo findings, CQ and TRA inhibited melanoma cell proliferation in vitro, which was correlated by decreased cyclin D1 expression. In addition, we found that tissues treated with CQ and TRA had significantly decreased numbers of CD4+ and CD8+ T-lymphocytes and F4/80+ macrophages. Together, these results indicate that cotreatment of CQ and TRA decreases cancer cell proliferation, but also dampens immune cell infiltration. Further study is warranted to understand whether CQ-induced immune suppression inadvertently affects therapeutic benefits.